148k views
2 votes
The graph below shows the function f(x)=x-3/x^2-2x-3 which statement is true

The graph below shows the function f(x)=x-3/x^2-2x-3 which statement is true-example-1
User RussKie
by
5.0k points

2 Answers

7 votes

Answer:

Its A. I just passed the final exam with 5 minutes left of the SESSION.

Explanation:

User Mbonato
by
6.3k points
2 votes

Answer:

The correct option is A.

Explanation:

Domain:

The expression in the denominator is x^2-2x-3

x² - 2x-3 ≠0

-3 = +1 -4

(x²-2x+1)-4 ≠0

(x²-2x+1)=(x-1)²

(x-1)² - (2)² ≠0

∴a²-b² =(a-b)(a+b)

(x-1-2)(x-1+2) ≠0

(x-3)(x+1) ≠0

x≠3 for all x≠ -1

So there is a hole at x=3 and an asymptote at x= -1, so Option B is wrong

Asymptote:

x-3/x^2-2x-3

We know that denominator is equal to (x-3)(x+1)

x-3/(x-3)(x+1)

x-3 will be cancelled out by x-3

1/x+1

We have asymptote at x=-1 and hole at x=3, therefore the correct option is A....

User Dom Free
by
5.4k points